SINERGI PCNA COLOMADU DAN GURU PUTRI AUM SE-COLOMADU DALAM PENDIDIKAN KESEHATAN REPRODUKSI UNTUK REMAJA - Dian Ardiyani (Tajdida: Jurnal Pemikiran dan Gerakan Muhammadiyah, 2020)
Adolescence is the spearhead in determining the future of a generation so that it needs to be prepared as well as possible to become the next generation that is advanced in various aspects of life. the process of adolescent development is not as smooth as we imagine, many sharp stones accompany the steps of adolescents in undergoing the process of maturity, especially on the issue of understanding reproductive health. This is important because if adolescents' understanding of reproductive health is lacking, it will have an impact on their future.Seeing these conditions, the Nasyiatul Aisyiyah Colomadu (PCNA) Branch Manager with Pashmina activities (Nasyiatul Aisyiyah Healthy Youth Service) in synergy with Muhammadiyah Charities (AUM) throughout Colomadu held a series of activities in the form of Reproductive Health seminars for female teachers at Muhammadiyah Schools. throughout Colomadu which will later become a provision for teachers in delivering education about reproductive health to their students